Method and system for sharing financial cost and income to households based on big data technology - LIU PIQIAN (2021)
The invention relates to the field of financial management accounting, in particular to a method, a device and a system for sharing financial cost and income to households based on a big data technology, electronic equipment and a computer readable storage medium. The method comprises the steps of: manually additionally recording data; then generating a customer manager expense table, a general ledger expense table, a reduction-and-division configuration table, a deduction project unit price table, a department-level motivation table, a conversion coefficient additional recording table, a customer list additional recording table, a unit price method configuration additional recording table, a unit price additional recording table, a profit and loss subject and expense large class mapping table and an expense large class project table; and automatically storing the data into a data warehouse after the additional recording. The method is high in overall efficiency and can meet the high-timeliness requirement of